Critical realism and Christianity: why no Christian should be a critical realist - Howe, Thomas (Peter Lang, 2025)
"This book is an exposition and analysis of Critical Realism, a philosophical approach that is quickly becoming the go-to position among Christian authors. Critical Realism poses a serious threat to Christian theology. Influential Christian authors argue for Critical Realism as an essential aspect of hermeneutic methodology. Evangelical scholars claim it has great potential for biblical studies. But as Howe shows, Critical Realism is incompatible with Christian doctrine. This book shows how Critical Realism conflicts with and subverts orthodox Christian theology and hermeneutics, and how it undermines Christian apologetics by blunting the possibility of deciding between the claims of conflicting and contradictory theologies and beliefs. This book is an effort to alert Christian authors to the dangers of adopting CR as a part of a Christian worldview. It will be of interest to all those committed to orthodox Christian theology and hermeneutics"--